Prevalence of 'being at risk of malnutrition' and associated factors in adult patients receiving nursing care at home in Belgium. Issue 5 (9th May 2014) - Geurden, Bart; Franck MPsych, Erik; Lopez Hartmann, Maja; Weyler, Joost; Ysebaert, Dirk
Abstract : Malnutrition is a known problem in hospitals and nursing homes. This study aims to evaluate the prevalence of being at risk of malnutrition in community living adults receiving homecare nursing and to determine factors independently associated with this risk of malnutrition. Furthermore, it also aimed to describe aspects of current nutritional nursing care. Patients ( n = 100) are screened with the Malnutrition Universal Screening Tool to evaluate their risk of malnutrition. A patient survey was used to analyse associated factors. In this population, 29% are at risk for malnutrition. Following a multivariate logistic regression analysis, 'loss of appetite' proved the most important factor. A survey for nurses ( n = 61) revealed low awareness, poor knowledge, poor communication between stakeholders and a moderate approach of malnutrition. These findings should encourage homecare nurses to use a recommended screening tool for malnutrition and to actively observe and report loss of appetite to initiate the prescription of individual tailored interventions. Belgian homecare nurses' management does not yet fully comply with international recommendations. Additional training in nutritional nursing care and screening methods for malnutrition is needed. Systematic screening should be further developed and evaluated in this at‐risk population.